ECOLOGICAL APPROACH TO THE ANALYSIS OF CONDITIONS OF FAMILY LIFE - E. V. Goltcova (Acta Biomedica Scientifica, 2013)
Ecology is the historical and evolutionary science that explores the nature of the system over time. Bringing people together and the family as a system is the central subject of social ecology as a science. An ecological approach is a general scientific approach that is driven by research and reflection relations and interactions of organisms and populations and in the special case of human society and the environment. The family is a social phenomenon, which is closely intertwined social and natural without losing its characteristics in the process of interaction, so the social ecology tries to show that well-being is based both on biological and social factors on well. In the historical and evolutionary changes of life of human communities transformation of the socio-economic status and quality of life of the family play a vital role. In the process of social development this transformations are the most significantly manifested in the emergence and resolution of conflicts between the growing needs of family groups and their capabilities to meet the conditions of the existing environment. Many of the vital needs of the individual can be met naturally only under specific roles and functions in the family as the primary basic social unit of society. A clear understanding of what environmental factors are and how to strengthen the family and to increase its resistance to stress, which, on the contrary, give rise to all sorts of dysfunction, reduced levels of well-being, and in the future, the degradation and even disintegration is required. Taking into account the dependence of family life on the implementation it is necessary to plan adequate social policies aimed at overcoming the crisis of the family, improving the quality of life. The development of such measures on the basis of an environmental approach can ensure the formation of a new family policy aimed at the preservation and development of a harmonious family. Currently in Russia there are prerequisites for the implementation of environmental paradigm of family as the foundation of society, because in Russia as a predominantly traditional society, the family suffered less erosion than in the West. Therefore, the family, which has appeared as a result of the crisis of civilization in the midst of all the negative, crisis processes, should be the center of attention of scientists, public figures and politicians, legislative and executive branches. The strategic goal of the state social policy must be seen above all in creating a prosperous financially, spiritually and intellectually well-off family, which should be developed for the sake of the relevant economic, political and social development strategy of the state.